An Ultra-Durable Windmill-Like Hybrid Nanogenerator for Steady and Efficient Harvesting of Low-Speed Wind Energy - Zhang, Ying; Zeng, Qixuan; Wu, Yan; Wu, Jun; Yuan, Songlei; Tan, Dujuan; Hu, Chenguo; Wang, Xue (Nano-Micro Letters, 2020)
Wind energy is one of the most promising and renewable energy sources; however, owing to the limitations of device structures, collecting low-speed wind energy by triboelectric nanogenerators (TENGs) is still a huge challenge. To solve this problem, an ultra-durable and highly efficient windmill-like hybrid nanogenerator (W-HNG) is developed. Herein, the W-HNG composes coupled TENG and electromagnetic generator (EMG) and adopts a rotational contact-separation mode. This unique design efficiently avoids the wear of friction materials and ensures a prolonged service life. Moreover, the generator group is separated from the wind-driven part, which successfully prevents rotation resistance induced by the friction between rotor and stator in the conventional structures, and realizes low-speed wind energy harvesting. Additionally, the output characteristics of TENG can be complementary to the different performance advantages of EMG to achieve a satisfactory power production. The device is successfully driven when the wind speed is 1.8 m s−1, and the output power of TENG and EMG can achieve 0.95 and 3.7 mW, respectively. After power management, the W-HNG has been successfully applied as a power source for electronic devices. This work provides a simple, reliable, and durable device for improved performance toward large-scale low-speed breeze energy harvesting. Highlights： 1 A novel windmill-like hybrid nanogenerator with contact-separation structure was proposed for harvesting breeze energy at low wind speed. 2 A spring steel sheet was creatively used both as an electrode of triboelectric nanogenerator and a booster for contact-separation activity. 3 A magnetic acting as a bifunctional element supplies magnetic flux variation in electromagnetic generator and overcomes electrostatic adsorption between tribolayers simultaneously.